Pisarenko V.G., Sorokatiy R.V., Dykha O.V., Babak O.P. Models of accumulation of tribodamages in cylindrical sliding tribosystems - Сорокатий, Р. В.; Писаренко, В. Г.; Диха, О. В.; Бабак, О. П. (Problems of Tribology, 2018)
Taking into account the peculiarities of wear processes, materials and conditions of the tribo conjugation, in most cases it is assumed that the instantaneous stress field affects the cracks development trajectory: less than the properties of the damaged material, and the characteristic development time of the crack is less than the characteristic time of accumulation of damage. The constructed lines of levels of the function of accumulation of damage, using probabilistic model, determined the most probable directions of trajectories of the propagation of cracks, estimated the type of destruction and the nature of the wear process. In modeling of wear processes, the most important and difficult task is to study the causes, mechanisms and kinetics of the formation of the surface layer during friction. Solving this problem allows you to manage the processes occurring on the contact. Together with the friction characteristics and durability, it opens up new opportunities in developing technologies that allow the formation of surface layers with the required characteristics. In order to estimate the type and nature of the fractures during wear-contact interaction of friction pairs, it is proposed to use the trajectories of the most intense accumulation of tribological damages. They are built in the direction of minimizing the accumulated damage. To construct trajectories of intense tribo damage along the points of the lines of the level of the tribological damage function, a cubic spline approximation is used. By estimating the spline error approximation, the minimum required number of isolation functions of the damage is determined to achieve a certain accuracy with a minimum amount of computational work